Slangs Used by Characters in Movie Script "I Hope They Serve Beer in Hell" - Ari Purnama, I Putu Agus; Suardhana, I Wayan; Sedeng, I Nyoman (Humanis; Vol 23 No 2 (2019), 2019)
This paper is entitled Analysis of Slangs Used by Characters in Movie Script “I Hope They Serve Beer in Hell”. The aims of this study are to identify and classify based on the types of slang word, this paper also described the context of situation of slang used in the movie script I Hope They Serve Beer in Hell. The data source was taken from the movie script I Hope They Serve Beer in Hell (2009). The data collection was conducted through library research method and note taking technique. The first step was done through reading attentively, noting the slang word, and classifying based on the types of slang and context of situation. The collected data were analyzed using descriptive qualitative method with the theory of Allan and Burridge (2006) for types of slang and theory of context of situation proposed by Holmes (2013). The result of analysis shows that there are four types of slang used by character in I Hope They Serve Beer in Hell movie script. Meanwhile, for the context of situation there are four components. The meaning behind each slang words and phrases in I Hope They Serve Beer in Hell movie script depends on the context of situation. Besides, the interpretation of meaning takes important roles in the analysis.